2016
DOI: 10.1016/j.molp.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b5 Reductase 1 Triggers Serial Reactions that Lead to Iron Uptake in Plants

Abstract: Rhizosphere acidification is essential for iron (Fe) uptake into plant roots. Plasma membrane (PM) H(+)-ATPases play key roles in rhizosphere acidification. However, it is not fully understood how PM H(+)-ATPase activity is regulated to enhance root Fe uptake under Fe-deficient conditions. Here, we present evidence that cytochrome b5 reductase 1 (CBR1) increases the levels of unsaturated fatty acids, which stimulate PM H(+)-ATPase activity and thus lead to rhizosphere acidification. CBR1-overexpressing (CBR1-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
(87 reference statements)
2
20
0
Order By: Relevance
“…In all eukaryotes, CYR1 provides electrons, via cytochrome b5, for a range of biochemical reactions in cellular metabolism, including for fatty acid desaturation in the endoplasmic reticulum [67]. It is well documented that CYR1 has a crucial role in increasing the level of unsaturated fatty acids, which activates PM-H + -ATPase and, thus, reduces rhizosphere pH [68]. The results obtained from this study suggested that this protein might be involved in response to adversely environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In all eukaryotes, CYR1 provides electrons, via cytochrome b5, for a range of biochemical reactions in cellular metabolism, including for fatty acid desaturation in the endoplasmic reticulum [67]. It is well documented that CYR1 has a crucial role in increasing the level of unsaturated fatty acids, which activates PM-H + -ATPase and, thus, reduces rhizosphere pH [68]. The results obtained from this study suggested that this protein might be involved in response to adversely environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, the accumulation of Cr was much higher in roots than in shoots. The taken up TEs accumulate in greater amounts in the roots than in the shoots, proportionately to the increase of concentration in the soil, with up to 70–98% of the taken up metals remaining in the roots [ 39 ]. The uptake of metals from the soil into the roots is dependent on the bioavailability of the metal, as well as its mobility in the rhizosphere [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of AHAs regulation remains unknown. Recent findings indicate that cytochrome B5 reductase 1 (CBR1) is able to activate plasma membrane-localized H + -ATPases, which is achieved by facilitating the content of unsaturated fatty acids [12]. CBR1 expression is induced under iron-deficient conditions.…”
Section: Iron Acquisition From Soil To Rootsmentioning
confidence: 99%
“…FAD2 is responsible for converting oleic acid (18:1) to linoleic acid (18:2), and FAD3 contributes to the conversion of 18:2 to linolenic acid (18:3). On the other side, 20 or 50 μM of the unsaturated fatty acids 18:2 or 18:3 can strongly activate H + -ATPase [12]. Other compounds such as phenolics, organic acids, flavonoids, and flavins have also been implicated in the acidification–reduction strategy to uptake iron (Strategy I) [3,13,14,15].…”
Section: Iron Acquisition From Soil To Rootsmentioning
confidence: 99%